DAMPAK PEMBANGUNAN IBU KOTA NUSANTARA (IKN) TERHADAP EKONOMI, SOSIAL, DAN LINGKUNGAN - Fadla Nilan (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2025)
The development of the Capital City of the Archipelago (IKN) is triggered by the need for equitable development in Indonesia and is planned to be a special area as the center of government and green innovation. IKN is located between Kutai Kertanegara Regency and Penajam Paser Utara Regency, East Kalimantan. This study aims to analyze the impact of IKN (Capital City of the Archipelago) development on the surrounding economy, social and environment. This study uses a literature study method with journal data related to the topic of discussion, published, and selected in the period starting from 2018 to 2023. The stages of the literature study carried out, namely listing the study variables, determining the source of information, selecting the description of the required materials, conducting a keyword search. The results of the literature study are used as reference material so as to provide an overview of the positive impacts and negative impacts of the IKN development, both those that have occurred and are still a potential that can occur. Based on the literature study, the relocation of IKN has both positive and negative impacts on several aspects: 1) Economic aspects, namely the potential for economic growth (positive) and the potential for additional inflation (negative), 2) social aspects, namely acculturation (positive) and inculturation (negative), and 3) the environment, namely the loss of natural habitat. Any potential negative impacts from the relocation of IKN can be prevented by finalizing the most effective planning and new solutions.